CONCEPTUAL FRAMEWORK FOR VIRTUAL TEAMS WITH REFERENCE TO ARTIFICIAL INTELLIGENCE AND EMPLOYEE ENGAGEMENT - Saxena, Parul; Rathore, Dr. B.S. (The journal of contemporary issues in business and government, 2022)
Covid-19 has brought a lot of changes in the organization structure from the working style to Employee Engagement. IT based technology has overtaken the market and is playing a crucial role in engagement of virtual teams. This research aims to see whether the use of AI-based technology, tools, and software can help management detect intangible things such as employee engagement level and provide clues as to what factors influence it and how management can improve it with special reference to virtual teams. This paper does systematic literature review which has twofold purpose: to identify the role of artificial intelligence in employee engagement in general and on virtual team in particular, and also the role of employee engagement in virtual teams and other purpose is to propose a theoretical model that can be useful for future research. This research is a qualitative approach. Research connected with the subject available till November 2021 has been reviewed using electronic databases such as ABI/INFORM Complete, EBSCO, Emerald Insight, ProQuest, SAGE Journals, Science Direct (Elsevier), Scopus, Springer Link, Taylor and Francis Online, Wiley Online Library. This research has shown that the use of AI based software can ingnificantly help management, not only to find out the status of each employee’s level of involvement but also to anticipate their attitudes and behaviors through predictive indicators. Thus, the company can proactively retain key employees. This research provides new and practical insights and opportunities for company owners and leaders to utilize technology to detect something that is naturally quite difficult because it requires specific knowledge and experience.